Efficient ortho-formylation in vitamin E series, application to the semi-synthesis of natural 5- and 7-formyl-δ-tocotrienols revealing an unprecedented 5-bromo-7-formyl exchange. Issue 49 (7th December 2017) - Alsabil, Khaled; Viault, Guillaume; Suor-Cherer, Sorphon; Helesbeux, Jean-Jacques; Merza, Joumaa; Dumontet, Vincent; Peña-Rodriguez, Luis Manuel; Richomme, Pascal; Séraphin, Denis
Abstract: Semi-synthesis of 5- and 7-formyltocopherols and tocotrienols has been developed by ortho -formylation of C-5 or C-7-unsubstituted vitamin E derivatives (14 examples) up to 90% yield, through heating in the presence of respectively 10-10-15 equivalents of MgCl2 -Et3 N-(CH2 O)n . Formylation of 5-bromo-δ-tocotrienol revealed an unprecedented 5-bromo/7-formyl exchange and yielded 7-bromo-5-formyl-δ-tocotrienol as major product. The minor 5-bromo-7-formyl-δ-tocotrienol led in three steps to 7-formyl-δ-tocotrienol previously isolated from the stem bark of Garcinia virgata . Graphical abstract: